The effect of intragroup communication on preference shifts in groups - Michael P. Brady; Steven Y. Wu (Institute for the Study of Labor (IZA), 2008)
We use a laboratory gift-exchange game to examine decisions made by groups under three different procedures that dictate how group members interact and reach decisions in comparison to individuals acting alone. We find that group decisions do deviate from those of individuals, but the direction and magnitude of gift exchange depend critically on the procedure. This suggests that no general statements can be made concerning the propensity of groups to exhibit reciprocal or other-regarding behavior relative to individuals. The rules governing how group members can express their preferences and expectations to other group members are critical for determining group outcomes.
urn:nbn:de:101:1-2008040941
Keywords: C91; 650; Group behavior; teams; decision making; social preferences; Gruppenentscheidung; Gruppenarbeit; Spieltheorie; Kommunikation; Soziale Wohlfahrtsfunktion; Test